Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 205527 by MATHEMATICSAM last updated on 23/Mar/24

If the roots of ax^2  + bx + c = 0 are one  another′s cube then show that  (b^2  − 2ac)^2  = ac(a + c)^2 .

Iftherootsofax2+bx+c=0areoneanotherscubethenshowthat(b22ac)2=ac(a+c)2.

Answered by A5T last updated on 23/Mar/24

Let the roots be α and β. Then, α=β^3  and β=α^3   α+β=α+α^3 =((−b)/a);αβ=α^4 =(c/a)⇒α=+_− ((c/a))^(1/4)   ⇒+_− ((c/a))^(1/4) +_− ((c^3 /a^3 ))^(1/4) =((−b)/a)⇒(√(c/a))+(√(c^3 /a^3 ))+((2c)/a)=(b^2 /a^2 )  ⇒(c/a)+(c^3 /a^3 )+((2c^2 )/a^2 )=(((b^2 −2ac)^2 )/a^4 )  ⇒a^3 c+ac^3 +2a^2 c^2 =ac(a+c)^2 =(b^2 −2ac)^2

Lettherootsbeαandβ.Then,α=β3andβ=α3α+β=α+α3=ba;αβ=α4=caα=+ca4+ca4+c3a34=baca+c3a3+2ca=b2a2ca+c3a3+2c2a2=(b22ac)2a4a3c+ac3+2a2c2=ac(a+c)2=(b22ac)2

Answered by Rasheed.Sindhi last updated on 24/Mar/24

AnOther Way  (b^2  − 2ac)^2  = ac(a + c)^2   ⇔(a^2 ((b^2 /a^2 ) − ((2ac)/a^2 )))^2  = ac(a((a/a) + (c/a)))^2   ⇔a^4 ((−(b/a))^2  −2( (c/a)))^2  = a^3 c(1 + (c/a))^2   ⇔((−(b/a))^2  −2( (c/a)))^2  = ((a^3 c)/a^4 )(1 + (c/a))^2   ⇔((−(b/a))^2  −2( (c/a)))^2  = (c/a)(1 + (c/a))^2   ⇔((α+β)^2  −2(αβ))^2  = αβ(1 + αβ)^2   ⇔(α^2 +β^2  )^2  = αβ(1+2αβ + α^2 β^2 )  ⇔α^4 +2α^2 β^2 +β^4   = αβ+2α^2 β^2  + α^3 β^3      α^3 =β ,β^3 =α⇒α^3 β^3 =αβ    α^4 =α∙α^3 =αβ , β^4 =β^3 ∙β=αβ  ⇔αβ+2α^2 β^2 +αβ  = αβ+2α^2 β^2  + αβ  ⇔2αβ+2α^2 β^2   =2 αβ+2α^2 β^2    Hence proved

AnOtherWay(b22ac)2=ac(a+c)2(a2(b2a22aca2))2=ac(a(aa+ca))2a4((ba)22(ca))2=a3c(1+ca)2((ba)22(ca))2=a3ca4(1+ca)2((ba)22(ca))2=ca(1+ca)2((α+β)22(αβ))2=αβ(1+αβ)2(α2+β2)2=αβ(1+2αβ+α2β2)α4+2α2β2+β4=αβ+2α2β2+α3β3α3=β,β3=αα3β3=αβα4=αα3=αβ,β4=β3β=αβαβ+2α2β2+αβ=αβ+2α2β2+αβ2αβ+2α2β2=2αβ+2α2β2Henceproved

Answered by Rasheed.Sindhi last updated on 24/Mar/24

Still another way  α+β=α+α^3 =−(b/a)⇒ determinant (((b=−aα^3 −aα)))  αβ=αα^3 =α^4 =(c/a)⇒ determinant (((c=aα^4 )))  (b^2  − 2ac)^2  = ac(a + c)^2   ⇒((−aα^3 −aα)^2  − 2a(aα^4 ))^2  = a(aα^4 )(a + aα^4 )^2   ⇒(a^2 (α^3 +α)^2  − 2a^2 α^4 ))^2  = a^2 (a^2 α^4 )(1 + α^4 )^2   ⇒a^4 ((α^6 +2α^4 +α^2 ) − 2α^4 ))^2  = (a^4 α^4 )(1 + α^4 )^2   ⇒a^4 ((α^6 +α^2 ) ))^2  = a^4 α^4 (1 + α^4 )^2   ⇒a^4 (α^(12) +2α^8 +α^4 = a^4 α^4 (1+2α^4  + α^8 )  ⇒a^4 (α^(12) +2α^8 +α^4 )= a^4 (α^4 +2α^8  + α^(12) )  Hence proved

Stillanotherwayα+β=α+α3=bab=aα3aααβ=αα3=α4=cac=aα4(b22ac)2=ac(a+c)2((aα3aα)22a(aα4))2=a(aα4)(a+aα4)2(a2(α3+α)22a2α4))2=a2(a2α4)(1+α4)2a4((α6+2α4+α2)2α4))2=(a4α4)(1+α4)2a4((α6+α2)))2=a4α4(1+α4)2a4(α12+2α8+α4=a4α4(1+2α4+α8)a4(α12+2α8+α4)=a4(α4+2α8+α12)Henceproved

Terms of Service

Privacy Policy

Contact: info@tinkutara.com